The Reputation Quotient as a Corporate Reputation Measurement in the Malaysian Banking Industry: A Confirmatory Factor Analysis - Dwi Sunu Kanto, Slamet Widodo; Ernest Cyril, de Run; Abu Hassan, Md. Isa (Elsevier Ltd., 2016)
The Reputation Quotient is one of the popular measurements for corporate reputation. It has been tested within a cross-cultural setting among countries in the United States, Europe and Australia. However, there is no reliable evidence that the Reputation Quotient is fit for Malaysia. The purpose of this paper is to empirically examine the Reputation Quotient model when it was applied to measure corporate reputation for the Malaysian banking industry. We resort to the standard confirmatory factor analysis tests. Workplace environment dimension was found weaker in the second order test. This paper seeks to introduce Reputation Quotient studies in Malaysia.